PERAN SELF-ESTEEM TERHADAP PERILAKU KONSUMTIF DENGAN KONFORMITAS SEBAGAI MEDIATOR PADA DEWASA AWAL PENGGUNA E-COMMERCE - Wijaya, Rysnawaty; Kurniawati, Meike; ninawati, ninawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Clothing can affect the level of self-confidence and self-esteem of individuals. This affects individual buying behavior, such as buying clothes and accessories to keep up with the latest fashion trends or it called consumptive behavior. Today's buying activities can be done easily, quickly, and anywhere through e-commerce. Trends that exist around individuals spread through several social groups. The existence of social groups also influence individuals in their behavior to adjust and want to be the same as them or also called conformity. Therefore, this study aims to determine the role of self-esteem on consumptive behavior with conformity as a mediator in early adult e-commerce during the COVID-19 pandemic. The study had 235 research participants ranging in age from 18 to 28 years, domiciled in Jakarta, Bogor, Depok and Tangerang (Jabodetabek), and shopped using e-commerce applications within the last 3 months. Based on the results of the regression analysis of conformity, self-esteem and consumptive behavior, the results obtained are F value (2, 234) = 105,609, p = 0.000, R2 = 0.477 the results indicate that their is a significant role for conformity and self-esteem together by 47.7% towards consumptive behavior in early adulthood. Based on the results of the analysis of the role of conformity as a mediator, the results of the indirect effect of self-esteem on consumer behavior = 0.2622, BootLLCI = 0.2325, BootULCI = 0.3556, direct effects = .0805, LLCI = -.0154, ULCI = 0.1764. The results show that self-esteem affects consumptive behavior in early adulthood because it increases conformity.